My chapter 3 test is tomorrow! help!

Thank you for the opportunity to help you with your question!

25k^2 - 36y^2

= 5^2k^2 - 6^2y^2 (write 25 = 5^2 and 36 = 6^2)

= (5k)^2 - (6y)^2

= (5k+6y) (5k-6y) use formula a^2 - b^2 = (a+b)(a-b)

Hence, the factors of given equation are (5k+6y) (5k-6y)

This is the Difference of two squares correct?

Correct. I have provided the formula and explanation alongside

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up